The Role of Lecturer Commitment in Determining Organisational Behaviour - Adriani Gunawan; Masydzulhak Djamil MZ; Farida Elmi; Setyo Riyanto (Asian Journal of Business and Accounting, 2023)
Manuscript type: Research paper Research aims: This study aims to examine the direct and indirect effects of servant leadership and perceived organisational support on organisational citizenship behaviour through the mediator of lecturer commitment. Design/Methodology/Approach: The research adopts a quantitative approach. Lecturers from private universities in regional higher education service institutions (LLDIKTI) III DKI Jakarta, Indonesia formed the research population. Purposive sampling was employed as the sampling technique. Data collection involved surveys using a questionnaire as the research instrument. Data analysis was conducted using SEM-PLS. Findings: The results demonstrate that servant leadership and perceived organisational support positively and significantly influence lecturer commitment and organisational citizenship behaviour. However, lecturer commitment does not significantly mediate servant leadership or perceived organisational support and organisational citizenship behaviour. Research limitations/Implications: Further research could examine other variables that can mediate servant leadership and perceived organisational support on organisational citizenship behaviour. Practical implications: The managerial implication suggests that university management should prioritise servant leadership and lecturer commitment to enhance lecturers’ performance of extra roles (organisational citizenship behaviour). Originality/Value: This study shows that lecturer commitment does not significantly mediate servant leadership or perceived organisational support and organisational citizenship behaviour.